It Is a Wild World in the City: Urban Wildlife Conservation and Communication in the Age of COVID-19 - Ioana A. Coman; Caitlyn E. Cooper-Norris; Scott Longing; Gad Perry (Diversity, 2022)
Most ecosystems are increasingly being degraded and reduced by human activities at the local and global scales. In contrast, urban environments are expanding as increasing portions of humanity move into cities. Despite the common perception among biologists that urban areas are biological deserts, cities offer habitat for many non-human species, but their ecology and conservation remain poorly studied. In this review, we first provide an update on the current state of knowledge on urban wildlife, then briefly examine the indirect effects of the COVID-19 pandemic on urban wildlife and add four components not previously included in comprehensive reviews. (1) We show that by reducing human activity, COVID-19 has temporarily enhanced urban habitat quality for some species and diminished it for others. (2) Thoughtful horticulture can contribute to urban wildlife by providing complex habitat structures that benefit biodiversity while enhancing human wellbeing. (3) Recent literature on urban invertebrate biodiversity has grown, though is still focused on pollinators. (4) Finally, employing insights from the discipline of communication can enhance the success of urban biodiversity conservation among both biologists and the public.